Carbonated beverages the incredibly disgusting story - Furgang, Adam (New York, NY : Rosen Central, 2011)
This book describes how carbonated soft drinks contribute up to 10 percent of young people's daily calories and how almost no nutritional value goes along with these calories that come from high fructose corn syrup, phosphoric acid, caffeine, and various flavors.
That's why it's called junk food -- Short-term effects -- Long-term effects -- Get healthy now!
1220L
Keywords: Food habits; Carbonated beverages -- Health aspects; Carbonated beverages